COLLECTIVE BEHAVIOUR AND INTERGROUP AGGRESSION - - Faturochman (Faculty of Psychology Universitas Gadjah Mada, 1999)
Crowd phenomena has challenged social psychology for about a century, even early development of social psychology has been inspired by the crowd phenomena. LeBon’s (citedin Moscovici, 1986 ; Reicher, 1996) book, The Crowds A Study of the Popular Mind, has been described by social psychologists as the most popular book of all time. His theory asserts thatindividuals in the crowd lose their conscious personality and that will lead to impulsive actions. The other characteristics of the crowds are mobile, and irritable, suggestible and credulous,exaggeration and ingenuousness. After LeBon, McDougall (in Farr, 1986) developed a concept of crowd, called group mind theory. Generally speaking, group mind theory has manysimilarities to LeBon’s theory and their successor such as Milgram and Toch (1969).